Más allá de la entrevista. Consideraciones sobre el uso de fuentes orales en la investigación histórica - Laura Pasquali (Nuevo mundo - Mundos Nuevos, 2014)
This paper presents some considerations on the oral sources and oral history, crossed by the assumption that they are vaster areas those of methodology. With this perspective some problems are deployed around the experiences that the interview provides to oral historians, the relevance of the hermeneutic approach to assess the text that produces the interview, the pertinence of qualitative methodologies for addressing memoirs and the stories they originate.